Relationship between starch fine structure and simulated oral processing of cooked japonica rice - Liu, Guodong; Wang, Ruizhi; Liu, Shaoqiang; Xu, Man; Guo, Lunan; Zhang, Hongcheng; Wei, Haiyan (Frontiers in Nutrition, 2022)
Background: Simulated oral processing can be used to evaluate the palatability of cooked rice. Previously, we established a simulated oral processing method using a texture analyzer equipped with a multiple extrusion cell probe (TA/MEC). However, the relationship between oral processing and starch fine structure remains unknown. Methods: In this study, we analyzed the oral processing properties using TA/MEC and characterized the starch fine structure of japonica rice by size-exclusion chromatography (SEC) and fluorophore-assisted capillary electrophoresis (FACE). The relationship between starch fine structure and oral processing of cooked japonica rice was further investigated. Results: Cooked rice structure contains fast-breakdown (Type I structure), slow-breakdown (Type II structure) and unbreakable structures (Type III structure). Fast-breakdown and slow-breakdown structure were positively correlated with the content of amylose and shorter amylopectin branches. The content of longer amylopectin branches was positively correlated with the contribution of unbreakable structure. Conclusion: The results indicated that cooked japonica rice varieties with more amylose and shorter amylopectin branches tend to form a harder texture and need more work to break down the fast and slow breakdown structures related to rice kernel fragmentation. Meanwhile, cooked japonica rice varieties possess stronger molecular entanglements due to their longer amylopectin branches and contribute more to the breakdown of unbreakable structures. These results can guide breeders to select rice varieties with desirable eating qualities for cultivation.